2006
DOI: 10.2174/092986706778201602
|View full text |Cite
|
Sign up to set email alerts
|

Breathing Generation and Potential Pharmacotherapeutic Approaches to Central Respiratory Disorders

Abstract: Breathing is generated and controlled by a brainstem neuronal network. Both intrinsic and synaptic interactions are involved in respiratory rhythm generation and their contribution is state-dependent, changing with hypoxia and the neuromodulatory state. Cellular mechanisms involved in acute or chronic pathological conditions are still unknown. A dysfunction in the neuronal network that controls breathing may be involved in several respiratory disorders such as central sleep apnea, sudden infant death syndrome,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
2

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 268 publications
(420 reference statements)
1
22
0
2
Order By: Relevance
“…Our study confirmed the feasibility of automated cardiorespiratory measurements as biomarkers of treatment response (40). It also indicates that these breathing evaluations may be more reliable and valid than clinical instruments because parent questionnaire data were in disagreement with clinicians' observations.…”
Section: Discussionsupporting
confidence: 71%
“…Our study confirmed the feasibility of automated cardiorespiratory measurements as biomarkers of treatment response (40). It also indicates that these breathing evaluations may be more reliable and valid than clinical instruments because parent questionnaire data were in disagreement with clinicians' observations.…”
Section: Discussionsupporting
confidence: 71%
“…However, alterations in the breathing-related modulation of hypoglossal motoneurons have been considered to be involved in sleep obstructive apnea [28][29][30]. Previous studies have shown that during specific experimental conditions, such as hypercapnia-hypoxia or lung inflation, the XII rhythmic activity might not be perfectly coupled to other respiratory motor outputs such as phrenic motoneurons [31,32].…”
Section: Discussionmentioning
confidence: 99%
“…Yet, we show here the first example of putative CRCs inhibited by hypocapnic hypoxia. The key evidence is that RTN photoinhibition no longer inhibited f R during hypoxia unless the plasma was reacidified with CO 2 or acetazolamide (Peña and García, 2006;Bell and Haouzi, 2010). Importantly, the difference between hypoxia and normoxia was Figure 12.…”
Section: Rtn Neurons: First Putative Crcs Demonstrably Silenced By Hymentioning
confidence: 99%
“…In reality, however, no CRC candidate (e.g., astrocytes, retrotrapezoid nucleus [RTN], serotonergic, orexinergic, and/or locus ceruleus neurons) has ever been shown to be inhibited by hypocapnic hypoxia. Hypocapnic hypoxia commonly produces sleep-disrupted breathing, a condition that improves with CO 2 supplementation or acetazolamide administration (Peña and García, 2006;Bell and Haouzi, 2010;Ainslie et al, 2013;Javaheri and Dempsey, 2013).…”
Section: Introductionmentioning
confidence: 99%